Distraction: an assessment of smartphone usage in health care work settings - Gill, Preetinder S (Dove Medical Press, 2012)
Smartphone use in health care work settings presents both opportunities and challenges. The benefits could be severely undermined if abuse and overuse are not kept in check. This practice-focused research paper examines the current panorama of health software applications. Findings from existing research are consolidated to elucidate the level and effects of distraction in health care work settings due to smartphone use. A conceptual framework for crafting guidelines to regulate the use of smartphones in health care work settings is then presented. Finally, specific guidelines are delineated to assist in creating policies for the use of smartphones in a health care workplace.